Human Coronavirus EMC Does Not Require the SARS-Coronavirus Receptor and Maintains Broad Replicative Capability in Mammalian Cell Lines - Müller, Marcel A. (American Society of Microbiology, 2012)
A new human coronavirus (hCoV-EMC) has emerged very recently in the Middle East. The clinical presentation resembled that of the severe acute respiratory syndrome (SARS) as encountered during the epidemic in 2002/2003. In both cases, acute renal failure was observed in humans. HCoV-EMC is a member of the same virus genus as SARS-CoV but constitutes a sister species. Here we investigated whether it might utilize angiotensin-converting enzyme 2 (ACE2), the SARS-CoV receptor. Knowledge of the receptor is highly critical because the restriction of the SARS receptor to deep compartments of the human respiratory tract limited the spread of SARS. In baby hamster kidney (BHK) cells, lentiviral transduction of human ACE2 (hACE2) conferred permissiveness and replication for SARS-CoV but not for hCoV-EMC. Monkey and human kidney cells (LLC-MK2, Vero, and 769-P) and swine kidney cells were permissive for both viruses, but only SARS-CoV infection could be blocked by anti-hACE2 antibody and could be neutralized by preincubation of virus with soluble ACE2. Our data show that ACE2 is neither necessary nor sufficient for hCoV-EMC replication. Moreover, hCoV-EMC, but not SARS-CoV, replicated in cell lines from Rousettus, Rhinolophus, Pipistrellus, Myotis, and Carollia bats, representing four major chiropteran families from both suborders. As human CoV normally cannot replicate in bat cells from different families, this suggests that hCoV-EMC might use a receptor molecule that is conserved in bats, pigs, and humans, implicating a low barrier against cross-host transmission.